The European Misery Report - Lee,Tiffany Lael (2019)
The burden of unhappy individuals in society is a vast and costly public health issue. Europe hosts some of the happiest countries in the world, but there are still many health inequalities. Given the connection between poor health and unhappiness, research must investigate the micro and macro determinants of a person’s life to better understand how policies can impact the lives and longevity of a population. To explore how self-rated health and other social determinants of health are associated with unhappiness across Europe. This study used cross-sectional data from the Round 8 (2016) European Social Survey of n = 41,830 adults across 22 European countries. The reported level of unhappiness was used as a dependent variable along with 15 explanatory variables considered as social determinants of health. Bivariate logistic regressions and multiple logistic regression were conducted to determine potential significant associations between unhappiness and various social determinants of health. Nagelkerke R Square and Cox & Snell R Square provided an indication of the amount of variation in the dependent variable that was explained by the final model. The strongest predictors for reporting unhappiness were poor self-rated health (AOR = 2.70, 95% CI 2.54 – 2.85), those struggling on their current income (AOR = 2.59, 95% 2.44 – 2.75), lacking social support (AOR = 1.97, 95% CI 1.77 – 2.20), those living in the Former USSR welfare regime (AOR = 1.94, 95% CI 1.77 – 2.12) and those who were separated/divorced or widowed (AOR = 1.84, 95% CI 1.72 – 1.97). The final model explained roughly 20 % of the variation in unhappiness across Europe. The findings indicate unhappiness being strongly associated with various social determinants of health including certain welfare regimes across Europe. Overall, the association between unhappiness and health needs further research to establish causality and minimize the prevalence of unhappiness across European countries.
Keywords: health; happiness; social determinants of health; multiple logistic regression; cross-sectional study; unhappiness; self-rated health; income status; welfare regimes; Europe; public health